Analysis of Student Learning Difficulties on Senior High School Scope of Biology - Ganis Sundawiyani; Kurnia Ningsih; Titin Titin (Universitas Negeri Padang Address: Biology Education Study Program Faculty Mathematics and Natural Science (FMIPA) Jl. Prof. Dr. Hamka Air Tawar Barat, Padang-West Sumatera-Indonesia Telp. +62751-7057420 - Fax.+62751-7058772 - Ph. +6281363229286, 2022)
This study aims to determine student learning difficulties, percentages, and the factors that cause learning difficulties experienced by class X students of SMA Negeri 6 Pontianak in studying the scope of biology. This research method uses a case study, with the research subjects being students of class X MIPA 3. In collecting data, three instruments were used, namely diagnostic tests, questionnaires, and interviews. The results showed that the percentage of students' learning difficulties in class X SMA Negeri 6 Pontianak in studying the scope of biology was 66.42% with high criteria. For the causal factors that affect student learning difficulties, it can be seen from the percentage of internal factors of 66.13% and external factors of 69.16% in the high category. Thus, class X SMA Negeri 6 Pontianak experienced learning difficulties caused by internal and external factors.